Considerations when devising a protocol for pre-eclampsia - O’Sullivan, Geraldine (Acta medica Lituanica, 2012)
Hypertension is the most frequent medical complication of pregnancy. Pre-eclampsia is one of the main causes of maternal and fetal morbidity and mortality. Hypertension is the most common first sign of preeclampsia. Pre-eclampsia is also associated with fetal growth restriction, low birth weight, preterm delivery, small for gestational age infants and respiratory distress syndrome.